Metabolically healthy obesity: epidemiology, mechanisms, and clinical implications - Stefan, Norbert; Häring, Hans-Ulrich; Hu, Frank B; Schulze, Matthias B (The lancet. Diabetes & endocrinology, 2013)
Obesity has become a worldwide epidemic that poses substantial health problems for both individuals and society. However, a proportion of obese individuals might not be at an increased risk for metabolic complications of obesity and, therefore, their phenotype can be referred to as metabolically healthy obesity. This novel concept of metabolically healthy obesity might become increasingly important to stratify individuals in the clinical treatment of obesity. However, no universally accepted criteria exist to define metabolically healthy obesity. Furthermore, many questions have been raised regarding the biological basis of this phenotype, the transitory nature of metabolically healthy obesity over time, and predictors of this phenotype. We describe the observational studies that gave rise to the idea of metabolically healthy obesity and the key parameters that can help to distinguish it from the general form of obesity. We also discuss potential biological mechanisms underlying metabolically healthy obesity and its public health and clinical implications.